Bibliometric Analysis of Sustainable Destinations - Loso Judijanto (West Science Interdisciplinary Studies, 2026)
This bibliometric analysis explores the evolution of research on sustainable destinations within the tourism industry, focusing on key trends and emerging themes from 2000 to 2025. Sustainable tourism, with its emphasis on long-term environmental, social, and economic benefits, has gained significant academic attention, reflecting the growing awareness of sustainability challenges in the tourism sector. The study analyzes a dataset of peer-reviewed articles from the Scopus database, applying bibliometric techniques such as co-authorship, co-citation, and keyword co-occurrence networks to map the field’s intellectual structure. Findings indicate that the literature on sustainable destinations is increasingly interdisciplinary, combining ecological conservation, community engagement, and responsible tourism practices. The study identifies key areas of focus, such as ecotourism, urban sustainability, and digital transformation through smart tourism technologies. It also highlights the role of sustainable destinations in advancing the United Nations Sustainable Development Goals (SDGs). The analysis provides insights into research gaps, the evolution of sustainable destination concepts, and opportunities for future interdisciplinary research to foster more integrated and resilient tourism practices.